The Correlation between C-Reactive Protein and Regulation of Glycemia in Type-2 Diabetic Patients - Mandal, Šačira; Čaušević, Adlija (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2017)
Inflammation plays a significant role in the development of Type 2 diabetes mellitus (T2D). Studies have indicated that C-reactive protein (CRP) as inflammatory marker is an important risk factor for insulin resistance (IR) and T2D. The purpose of this study was to determine concentrations of fasting C-reactive protein, glucose, and hemoglobin A1c (HbA1c) in a total of 40 adults with Type 2 diabetes (40-60 years of the age) and 40 healthy subjects as control group (the same ages). We found that C-reactive protein concentrations in diabetic subjects were higher than those in control group. Also, our results have shown the significant association between CRP and hemoglobin A1c levels (p0.05) in T2 diabetics. A negative, but not significant correlation of CRP with glucose and hemoglobin A1c levels was demonstrated in controls. Therefore, our findings suggest an association between glycemic control and systematic inflammation in people with diagnosed diabetes.